2005
DOI: 10.3147/jsfp.40.15
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Inactivated Virus Vaccine against Viral Nervous Necrosis (VNN)

Abstract: ABSTRACT-The efficacy of inactivated betanodavirus as a vaccine against viral nervous necrosis (VNN) was evaluated using juvenile sevenband grouper Epinephelus septemfasciatus.Fish were intraperitoneally injected once with formalin-inactivated redspotted grouper nervous necrosis virus (RGNNV). Virus-neutralizing antibodies were detected in the vaccinated fish from Day 10 to the end of the experimental period (Day 160), showing 1: 2,000 or higher mean antibody titers from Day 21 to Day 77. The vaccinated and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 26 publications
7
66
2
2
Order By: Relevance
“…vaccination system. The previous vaccination studies revealed that the recombinant coat protein or formalin-inactivated virus induced high and long duration of virus-neutralizing anti bodies and protection against virus challenges (Husgard et al, 2001;Tanaka et al, 2001;Yamashita et al, 2005). However, it takes 2 or more weeks to the onset of specific immunity against nodaviruses and thus there is a room for vaccine improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…vaccination system. The previous vaccination studies revealed that the recombinant coat protein or formalin-inactivated virus induced high and long duration of virus-neutralizing anti bodies and protection against virus challenges (Husgard et al, 2001;Tanaka et al, 2001;Yamashita et al, 2005). However, it takes 2 or more weeks to the onset of specific immunity against nodaviruses and thus there is a room for vaccine improvement.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no means to prevent the disease in older fish during net-pen culture, though the protective effects of the recombinant coat protein or inactivated virus vaccines were experimentally demonstrated (Tanaka et al, 2001;Yamashita et al, 2005).…”
mentioning
confidence: 99%
“…A betanodavirus SGEhi00 strain, which had been isolated from a diseased sevenband grouper in Japan and identified as RGNNV (31), was used in this study. The virus was propagated in E-11 cells cultured at 25°C in Leibovitz's L-15 medium (Life Technologies, USA) supplemented with 5% fetal bovine serum (FBS), as previously described (32).…”
Section: Fishmentioning
confidence: 99%
“…To ensure that the fish are as healthy as possible, a useful and practical approach would be vaccination of fish and boosting their immune system. Various types of vaccines have been developed such as formalininactivated vaccine, subunit vaccine with recombinant coat protein of betanodavirus and nodavirus-like particle vaccine [58,74,111,116,118,121,124]. Vaccination trials have shown protection efficacy against betanodavirus infection.…”
Section: Disease Control Strategiesmentioning
confidence: 99%